Effects of Hydrothermal and Microwave Dual Treatment and Zein on the Enzymolysis of High Amylose Corn Starch - Jie Liu; Qiuye Yang; Tiantian Yuan; Yawei Liu; Guihong Fang (Gels, 2022)
Resistant starch (RS) type 2-high-amylose corn starch (HACS) was subjected to simultaneous hydrothermal (25% moisture content, 90 °C for 12 h) and microwave (35% moisture content, 40 W/g microwaving for 4 min) treatment and zein (at a zein to treated starch ratio of 1:5, 50 °C for 1 h) to improve its resistance to enzymolysis. Scanning electron microscopy (SEM) highlighted the aggregation and adhesion of the composite. The average particle size of the composite (27.65 μm) was exceeded that of both the HACS (12.52 μm) and the hydrothermal and microwave treated HACS (hydro-micro-HACS) (12.68 μm). The X-ray diffraction results revealed that the hydro-micro-HACS and composite remained B-type, while their crystallinity significantly decreased to 16.98% and 12.11%, respectively. The viscosity of the hydro-micro-HACS and composite at 50 °C was 25.41% and 35.36% lower than that of HACS. The differential scanning calorimetry (DSC) results demonstrated that the composite displayed a new endothermic peak at 95.79 °C, while the weight loss rate and decomposition temperature were 7.61% and 2.39% lower than HACS, respectively. The RS content in HACS, the hydro-micro-HACS, and composite was 47.12%, 57.28%, and 62.74%, respectively. In conclusion, hydrothermal and microwave treatment combined with zein provide an efficient physical strategy to enhance the RS type 2-HACS.